Recent Advancements in the Management of Obesity - Hossain, Ahmed (Bangladesh Journal of Medicine, 2024)
Obesity is an increasing global health concern. Its worldwide prevalence continues to rise, estimated by the World Health Organization to have almost tripled since 1975 to affect more than 650 million adults in 2016. It is closely associated with severe chronic co-morbidities, which remain the leading causes of death. lifestyle changes alone rarely lead to sustained weight loss, particularly in this era of ‘obesogenic’ environment. Compared with lifestyle interventions alone, all medications approved for obesity management are more effective for long-term weight loss and improvements in cardiometabolic risk factors. Older obesity medications are associated with mean weight losses in the range of 5–10%. Some medications exhibit inadequate efficacy and dangerous side effects. Improved understanding of the gut-brain axis has inspired the pursuit of novel medications aiming to provide sustainable and safe weight loss. The new generation of agents, including the injectable incretin analogues semaglutide and tirzepatide are associated with sustained mean weight reductions of 15–20%, along with substantial benefits on a range of health outcomes. The combination pharmacotherapies have demonstrated significantly greater efficacy in weight loss compared to the individual drugs. Bariatric surgical methods are widely employed surgical interventions for treating obesity. They provide more effective and long-lasting outcomes but carry a relatively higher risk of complications, which limits their widespread adoption. Bariatric surgeries are considered the treatment of choice for patients with a BMI >40 kg/m2 or BMI >35 kg/m2 with severe associated comorbidities. Several novel endoscopic devices and procedures are promising due to their satisfactory results, relatively lower cost, and lower risk. As minimally invasive surgery is favored by patients, there has been significant development in endoscopic weight reduction procedures and devices. Several newer therapeutic approaches such as probiotics, topical lotions, transcatheter bariatric embolization, low insulin method, or gene therapy have gained attention. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 132